The comparison of the physical activity level in young adults assessed with measuring tools and subjective self-assessment - Popiołek, Joanna; Kusz, Monika; Alzubedi, Adam; Konopelko, Michał (Journal of Education, Health and Sport, 2018)
Daily physical activity is one of many factors determining health. World Health Organization (WHO) recommends regular moderate physical activity for people of all ages. The aim of this study was to compare the classified level of physical activity of young adults with their sub-jective self-assessment.The study group consisted of 42 people aged 20-24 years, on average 21.5 years. 62% (26 people) were women, and 38% (32 people) were men. Data was obtained using a paper ques-tionnaire based on the International Physical Activity Questionnaire (IPAQ). The respond-ents were asked about their physical activity during the week and their own assessment of their level of physical activity. 52.38% of respondents reported that they regularly exercise. Men do it more often (75% of men) and women less often (38.46% of women). 80.95% considered their own level of physi-cal activity as sufficient, 9.22% as high, and 9.52% as insufficient. At the same time, based on the IPAQ calculation, 42.86% respondents represented a sufficient level of physical activity, 38.10% high, and 19.05% insufficient. The average level of activity was 1668,57 MET-min/week, which according to the IPAQ classification means a high level of physical activity.In summary, young adults represent high levels of physical activity. The study showed that they tend to under- and overestimate their level of physical activity, whereas the underestima-tion is more common.